Dina. - MURPHY, KATE (New York Times, 2013)
The article focuses on Syrian Dina Katabi, professor of electrical engineering and computer science at the Massachusetts Institute of Technology, who was awarded a MacArthur genius grant for her contribution to improve the speed, reliability, and security of data networks in September 2013.